The causes of the Rising incidence of domestic violence in Nigeria: Proposing Judicial Separation as a Panacea - Paul Atagamen Aidonojie; Toyin Afolabi Majekodunmi; Oluwaseye Oluwayomi Ikubanni; Alade Adeniyi Oyebade; Nathan Ibrahim (Jurnal Hukum, 2022)
The increase in domestic violence in Nigeria has become overwhelming. However, the death of Osinachi Nwachukwu (a popular gospel artist singer), which has been linked to domestic violence, prompted the discussion of domestic violence to be more pronounced. Although several laws and institutional bodies are set up to curtail the incidence of domestic violence, there seems to be an increase in the monster in Nigeria. In this regard, this study adopts a hybrid method of research to ascertain the causes of the current increase in domestic violence in Nigeria and proposes judicial separation as a panacea. In this regard, various literature and laws were analysed concerning the suitability of judicial separation as a panacea in curtailing domestic violence. Furthermore 350 questionnaire was distributed to respondents to ascertain the causes of the current increase in domestic violence and possible solution. The study, therefore, found that alcohol abuse, psychological disorder, economic hardship, and traditional belief are some of the causes of the current increase in domestic violence in Nigeria. The study also found that judicial separation could be a viable legal tool to curtail domestic violence, given that it preserves the status quo of the marriage. Therefore, the study concludes and recommends that victims of domestic violence should open up and embrace the concept of judicial separation. Â